2000
DOI: 10.1086/309193
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Angular Distribution of the Intermediate Subclass of Gamma‐Ray Bursts

Abstract: In the article a test is developed, which allows to test the null-hypothesis of the intrinsic randomness in the angular distribution of gamma-ray bursts collected at the Current BATSE Catalog. The method is a modified version of the well-known counts-in-cells test, and fully eliminates the non-uniform skyexposure function of BATSE instrument. Applying this method to the case of 1 all gamma-ray bursts no intrinsic non-randomness was found. The test also did not find intrinsic non-randomnesses for the short and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 19 publications
3
69
0
2
Order By: Relevance
“…However, the physical existence of the third group is still argueable. The sky distribution of the third component is anisotropic as proven by Balázs et al (1998), Balázs et al (1999), Mészáros et al (2000), Litvin et al (2001). The log N− log S distribution may also differ from the other group's distributions (Horváth 1998).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the physical existence of the third group is still argueable. The sky distribution of the third component is anisotropic as proven by Balázs et al (1998), Balázs et al (1999), Mészáros et al (2000), Litvin et al (2001). The log N− log S distribution may also differ from the other group's distributions (Horváth 1998).…”
Section: Discussionmentioning
confidence: 90%
“…Further, the intermediate subgroup shows a remarkable angular distribution on the sky (Balázs et al 1998;Balázs et al 1999;Mészáros et al 2000;Litvin et al 2001 the existence of this subgroup is a matter of debate. Hence additional studies concerning this subclass are highly desireable.…”
Section: Introductionmentioning
confidence: 99%
“…As a further test, we compare the distribution of the dimmer intermediate bursts with that of the long bursts, because this pair of distributions were found by Mészáros et al (2000) to exhibit the strongest difference. To do this, we select the fainter 50% of the bursts, defined as those bursts with a fluence in the 15−25 keV band lower or equal to the median value of all the intermediate bursts (the same result is obtained by using the 50−100 keV band).…”
Section: Redshift Distributionmentioning
confidence: 99%
“…The large-scale angular isotropy of the sky distribution of GRBs has been well studied over the last few decades. Most of these studies have demonstrated that the sky distribution of GRBs is isotropic Tegmark et al 1996;Balázs et al 1998Balázs et al , 1999Mészáros et al 2000;Magliocchetti et al 2003;Vavrek et al 2008).…”
Section: Introductionmentioning
confidence: 99%